Practices to improve identification of Adult Antiretroviral Therapy failure at the Lighthouse Trust clinic in Lilongwe, Malawi - Vorkas, Charles Kyriakos (2011)
BACKGROUND: Evaluating treatment failure is critical when deciding to modify antiretroviral therapy (ART). Virologic Assessment Forms (VAFs) were implemented in July 2008 as a prerequisite for ordering viral load. The form requires assessment of clinical and immunologic status. METHODS: Using the Electronic Medical Record (EMR), we retrospectively evaluated patients who met 2006 WHO guidelines for immunologic failure (≥15 years old; on ART ≥6 months; CD4 count <baseline OR CD4 count >50% drop from peak OR CD4 persistently <100 cells) at the Lighthouse Trust clinic from 12/2007–12/2009. We compared virologic screening, VAF implementation and ART modification during the same period using Fisher’s exact tests and unpaired t-tests as appropriate. RESULTS: Of 7,000 enrolled ART patients ≥ 15 years old with at least two CD4 counts, 10% had immunologic failure with a median follow-up time on ART of 1.4 years (IQR: 0.8–2.3). Forty (6%) viral loads were ordered: 14 (35%) were detectable (>400 HIV RNA copies/mL) and 1 (7%) patient was switched to second-line therapy. Overall, 259 VAFs were completed: 67% for immunologic failure and 33% for WHO Stage 4 condition. Before VAF implementation, 1% of patients had viral loads drawn during routine care, whereas afterwards, 8% did (p<0.0001; 95% CI 0.03–0.08). CONCLUSIONS: Clinicians did not identify a large proportion of immunologic failure patients for screening. Implementation of VAFs produced little improvement in virologic screening during routine care. Better training and monitoring systems are needed.